Avaliação de índice proliferativo em amostras citopatológicas de tumores mamários caninos: correlação histopatológica - Morais, Dener Barros (2021)
The mammary gland is a modified apocrine sweat gland that has been observed in mammals for millions of years. It is subject to the development of tumors and, although the etiology is not very clear, several factors are associated with its development, such as hormones, nutrition, age and race. Neoplasms are among the main diseases that directly affect the mammary glands of bitches. Therefore, there was a need to use prognostic markers to identify the proliferative index of these tumors, such as argyrophilic nucleolar organizer regions (AgNOR), with the aim of helping to establish an adequate therapeutic protocol. This study aimed to investigate whether there is an agreement between the cytopathological evaluation by the tumor proliferative index, through the AgNOR technique, and the histopathological examination of mammary neoplasms in bitches. The samples collected by fine needle aspiration cytology (FNAC) were analyzed at the Laboratory of Veterinary Clinical Analysis of the Federal University of Santa Maria, and the histopathological examination was performed by the Laboratory of Veterinary Pathology within the same institution. Data were obtained from the analysis using computer software (IBM SPSS Statistics 23). The AgNOR count values of the cytological samples were correlated with the histopathological reports by a non-parametric Kruskal-Wallis test and the comparison between the AgNORs indices of two evaluators was also made using the Wilcoxon test for data analysis. It is considered that there were no differences in the mean AgNOR indexes of the different histological types of breast tumors for any of the evaluators, while the calculated p was greater than 0.05 and the comparison between the counts of the two evaluators showed that there was a difference because the p value was less than 0.05. We were able to conclude that further studies are needed with a larger number of samples and other prognostic markers that may help us to validate and complement the AgNOR technique.